Dosis de Trichoderma harzianum en las características agronómicas y rendimiento de rizomas de Cúrcuma longa, Loreto. 2023 - Lavado Solsol, Angie Verona (2024)
Curcuma (Curcuma longa) is a perennial herb plant with elongated and webbed roots or tubers, rough on the outside and brown on the outside and deep orange on the inside. Its rhizomes contain as main phytochemical compounds the curcuminoids which give it significant properties as a colorant, medicinal uses and a variety of industrial uses. The application of the Trichoderma harzianum fungus as described above constitutes one of the sustainable alternatives to improve the agronomic components and the quality of the rhizomes by facilitating a greater absorption of soil nutrients, improving tolerance to biotic and abiotic stresses and resistance to diseases. The effect of different doses of Trichoderma harzianum on the agronomic characteristics, yield and quality of Curcuma longa rhizomes was evaluated, using the experimental design of blocks completely randomized (DBCA), with 4 treatments and 5 replicates using regression analysis and R in the variables, as well as normality and homogeneity of variances tests. The treatments were: To: 0, T1: 2 g, T2: 4 g; T3: 6 g of substrate containing fungal spores. The doses significantly influenced where T3 (6 g) achieved a greater effect on the number of leaves with 46.82; while T1 (2 g) promoted a greater plant height with 62.24 cm as well as a greater number of new shoots with 1.32 and a greater shoot gain (0.56). In addition, T3 showed that the application of T. harzianum achieved the highest yields with 10.82 t/ha in fresh rhizomes and 1.46 t/ha in dry powder compared to 7.82 and 1.0 t/ha for the control, respectively. In terms of quality, T1 increased the curcuminoid content with 7.8 % compared to 6.59 % for the control; however, T3 increased the % of ash and fat to 17.35 and 16.77 % compared to 15.35 and 15.5 % for the control.